Sexual Behaviours for Contracting Sexually Transmitted Infections and HIV at Badung Traditional Market, Bali - Pradnyawati, Luh Gede; Ani, Luh Seri; Januraga, Pande Putu (Department of Public Health, Faculty of Sport Science, Universitas Negeri Semarang, 2019)
Studies on sexual behaviours are mainly conducted among high risk populations, only limited publications from female general population. This study aims to explore sexual behaviours among women who work at the biggest traditional market in Bali Province. A mix-methods approach was used to study women who work at the Badung Market in Bali. In October 2016, a survey of 100 women was conducted, then followed by a total of 20 in-depth interviews. Quantitative data were analysed using descriptive statistic, while qualitative data were analysed using thematic approach. Our survey found that 60% of respondents were perceived themselves as a low risk group. As many as 22% of respondents admitted that they had sexual intercourse with more than one partner over the last years with 41% of them used condom on their last sexual intercourse. In-depth interviews revealed that the basis of their sexual intercourse was mutual interests and desire. Only one respondent admitted economic reasons for sexual intercourse. Condoms were rarely used because of low risk perception of the sexual intercourse. Prevention programs targeting low risk groups are required to reduce the burden of disease from STIs including HIV.Ã‚Â